Coexistence of cellulitis and primary peritonitis in a pediatric patient with nephrotic syndrome: A case report - Luisa Lagos; Juan Valero (Elsevier, 2017)
Nephrotic syndrome is a chronic disease that increases the risk of skin, respiratory and urinary tract infection, while also increasing the chance for other diseases, like peritonitis and meningitis. A four year old patient with a history of nephrotic syndrome was admitted to emergency room (ER) with the following symptoms: abdominal pain, fever, diarrhea and vomiting, associated to abdominal wall erythema, abdominal distension and peritoneal signs. In order to make a differential diagnosis of the infection, peritoneal fluid was extracted and, according to the characteristics found, treatment with broad-spectrum antibiotics was started. Cases in which different infections like pneumonia, abdominal wall peritonitis and cellulitis occur simultaneously have been reported rarely. Early diagnosis and dismissal of other causes of acute abdominal pain, as well as early introduction of antibiotics are fundamental in the treatment of these kind of infections.